Stable isotope analysis spills the beans about spatial variance in trophic structure in a fish host – parasite system from the Vaal River System, South Africa. (August 2020) - Gilbert, Beric M.; Nachev, Milen; Jochmann, Maik A.; Schmidt, Torsten C.; Köster, Daniel; Sures, Bernd; Avenant-Oldewage, Annemariè
Abstract: Stable isotope analysis offers a unique tool for comparing trophic interactions and food web architecture in ecosystems based on analysis of stable isotope ratios of carbon ( 13 C/ 12 C) and nitrogen ( 15 N/ 14 N) in organisms. Clarias gariepinus were collected from six sites along the Vaal River, South Africa and were assessed for ectoparasites and endoparasites. Lamproglena clariae (Copepoda), Tetracampos ciliotheca and Proteocephalus glanduligerus (Cestoda), and larval Contracaecum sp. (Nematoda) were collected from the gills, intestine and mesenteries, respectively. Signatures of δ 13 C and δ 15 N were analysed in host muscle tissue and parasites using bulk stable isotope analysis. Variable stable isotope enrichment between parasites and host were observed; L. clariae and the host shared similar δ 15 N signatures and endoparasites being depleted in δ 13 C and δ 15 N relative to the host. Differences in stable isotope enrichment between parasites could be related to the feeding strategy of each parasite species collected. Geographic and spatial differences in enrichment of stable isotopes observed in hosts were mirrored by parasites. As parasites rely on a single host for meeting their nutritional demands, stable isotope variability in parasites relates to the dietary differences of host organisms and therefore variations in baseline stable isotope signatures of food items consumed by hosts. Graphical abstract: Image 1 Highlights: Stable isotope enrichment in parasites was variable compared to the host. Host fish and  Lamproglena clariae shared similar trophic level. Endoparasites were depleted in δ 13 C and δ 15 N compared to the host. Spatial differences in host stable isotopes were mirrored by parasites and related to host diet.